(untitled) (Global Journal of Management and Business Research, 2015)
This study was carried out to examine the major determinant of capital structure of quoted composite insurance companies in Nigeria. A descriptive and explanatory research designed was adopted for this study and the secondary data extracted from the annual report of the purposeful composite insurance was analysed using panel data regression technique. The results revealed that tangibility, growth and Liquidity had a negative impact on the Leverage while Risk, Return on Asset and Size have a positive influenced on Leverage; it was discovered from this study that all the variables identified are statistically significant except Return on Asset and growth; the model was reliable and appropriate for determining capital structure of composite insurance companies; It can be concluded that fixed effect panel regression model was better than the random effect model in determining the capital structure of composite insurance in Nigeria.